55‐1: Invited Paper: Beyond Flexible Towards Sustainable Electronics. Issue 1 (28th June 2021) - Vasara, Antti; Hakola, Liisa; Välimäki, Marja; Vilkman, Marja; Orelma, Hannes; Immonen, Kirsi; Torvinen, Katariina; Hast, Jukka; Smolander, Maria
Abstract : Sustainability and circular economy cover the principles of designing out waste and pollution, keeping products and materials in use, and regenerating natural systems. Due to global trends (eg. increasing e‐waste and material consumption) and global sustainability goals also electronics industry has to consider how to increase sustainability in its products, operations and service models. VTT has demonstrated sustainable electronic solutions by developing bio‐based and renewable material processing, by utilizing high‐speed printing and hybrid integration manufacturing processes, and by evaluating environmental impact of electronic systems and devices. This paper covers the different aspects of sustainability and highlights solutions demonstrated at VTT.